PERSEPSI DAN FAKTOR YANG MEMPENGARUHI KEPUTUSAN ORANGTUA UNTUK TIDAK MEMASUKKAN ANAKNYA KE PENDIDIKAN ANAK USIA DINI DI DESA TAMBUSAI KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Putra, Refandi Syah; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Education is one of the important things in society component. Every children mustget education since young. This is different with the society in Desa TambusaiKecamatan Rumbio Jaya Kabupaten Kampar. There are still many the youngchildren are not feel the play group. The play group in Desa Tambusai comeperception abaout it’s play group. It can see from the parents’ back ground thatmake’s the perception about play group. This research is done as the effort to tellparents’ perception about play group and the factor that impluence parents’decision for not entering their children to play group. Responden of the researchare parents are not entering play group they are 97 people. The writer usekuantitative descriftive method and the data is analyzed with kuantitative and usetotal quota sampling technique. The data instruments are observation, quisoner anddocumentation. From the research was done, the writer met respondent perceptionabout play group in the Desa Tambusai is positive with percentage is 68%. It meansthe parents and respondents in Desa Tambusai Kecamatan Rumbio JayaKabupaten Kampar agree with play group their children. From the result of thedata, parents participation to follow their children to the play group is still low withpwercentage 18,4%. The factor that impluence parents’ decision and responden fornot entering their children to play group is economic factor with percentage is 63%.Key Word : Perception, Parents’Decision, Play Group, Desa Tambusai